Efficacy of high-dissolution turmeric-sesame formulation for pain relief in adult subjects with acute musculoskeletal pain compared to acetaminophen: A randomized controlled study - Rudrappa, Girish H.; Chakravarthi, Pruthvi T.; Benny, Irin Rosanna (Medicine (Baltimore), 2020)
Acetaminophen (paracetamol) is one of the most commonly used over-the-counter for pain relief. Management of acute pain with plant-based nutrients has remained suboptimal due to an absence of data supporting acute relief of pain. In the present study, it was hypothesized that high-dissolution liquid treatment of black sesame extract oil, Curcuma longa and Boswellia serrata may provide pain relief in people with acute musculoskeletal pain as quickly as acetaminophen. In this randomized active controlled open label study, 88 healthy subjects with acute musculoskeletal pain were randomized to receive treatment capsule (Rhuleave-K; 1,000 mg/d) or 1,000 mg/d acetaminophen for 7 days. Change in pain intensity and pain relief at first 6 hours, 3 days, and 7 days were measured. The onset of analgesia was measured by perceptible pain relief and meaningful pain relief. Other measures were McGill Pain Questionnaire and Patient Global Impression Change. The treatment formulation resulted in average magnitude of pain relief comparable to the acetaminophen. Sixty-six percent of subjects in the treatment group reported positive response in pain relief (≥50% max TOTPAR; total pain relief) after 6 hours, compared to 73% of control. Seventy-three percent of subjects on treatment were considered positive responders, compared to 80% in the control group. The average time of onset of analgesia was 1 hour for the treatment group, versus 0.83 hour for control. At the end of day 3 and 7, there was significant improvement (P < .001 for day 3 and day 7) in the pain condition of treatment group and was comparable to control (P = .436 for day 3 and P = .529 for day 7). The total McGill Pain score showed significant reduction in pain with the treatment irrespective of the pain intensity statistically equal (P = .468) to control. Both the groups were equal in providing sensory pain relief (P = .942), but the treatment was 8.57 times significantly better (P = .027) than acetaminophen in reducing the unpleasantness and emotional aspects (affective domain) involved with acute pain. The results showed that the treatment used in the study may act as a natural, fast acting, and safe alternative for acute pain relief comparable to acetaminophen.